Low muscle mass is associated with early termination of chemotherapy related to toxicity in patients with head and neck cancer. Issue 2 (February 2020) - Sealy, Martine J.; Dechaphunkul, Tanadech; van der Schans, Cees P.; Krijnen, Wim P.; Roodenburg, Jan L.N.; Walker, John; Jager-Wittenaar, Harriët; Baracos, Vickie E.
Summary: Background & aims: We studied whether low pre-treatment muscle mass, measured with CT at thoracic (T4) or lumbar level (L3) associates with early termination of chemotherapy related to toxicity in head and neck cancer (HNC) patients. Methods: This was a retrospective chart and image review. Adult HNC patients treated with (surgery and) platinum-based chemo-radiotherapy were included if a pre-treatment CT scan at T4 or L3 level was available. Muscle mass was evaluated by assessment of skeletal muscle index (SMI; cm 2 /m 2 ). T4 and L3 SMI measurements were corrected for deviation from their respective means and were merged into one score for SMI difference (cm 2 /m 2 ). All cases were assessed for presence of toxicity-related unplanned early termination of chemotherapy ('early termination'). Univariate and multivariate logistic regression models were used to investigate associations between pooled SMI and early termination. Results: 213 patients (age: 57.9 ± 10.3 y, male: 77%, T4 image: 45%) were included. A significant association between SMI as a continuous variable and early termination was found, both in the univariate analysis (p = 0.007, OR = 0.96 [0.94–0.99]) and the multivariate analysis (p = 0.021, OR 0.96 [0.92–0.99]). The multivariate models identified potential associations with type of chemotherapy, presence of co-morbidity, a combination of (former) smoking and alcohol consumption, and sex. Conclusion: Lower muscle mass was robustly associated with higher odds of early termination of chemotherapy in HNC patients. Further prospective studies are required to tailor the care for patients with low muscle mass and to avoid early termination of chemotherapy.